Glomerular Filtration Rate and/or Ratio of Urine Albumin to Creatinine as Markers for Diabetic Retinopathy: A Ten-Year Follow-Up Study - Pedro Romero-Aroca; Marc Baget-Bernaldiz; Raul Navarro-Gil; Antonio Moreno-Ribas; Aida Valls-Mateu; Ramon Sagarra-Alamo; Joan F. Barrot-De La Puente; Xavier Mundet-Tuduri (Journal of Diabetes Research)
Aims. To determine the relationship between diabetic nephropathy and diabetic retinopathy on a population of type 2 diabetes mellitus patients. Methods. A prospective ten-year follow-up population-based study. We determined differences between estimated glomerular filtration rate (eGFR) using the chronic kidney disease epidemiology collaboration equation and urine albumin to creatinine ratio. Results. Annual incidence of any-DR was 8.21 ± 0.60% (7.06%–8.92%), sight-threatening diabetic retinopathy (STDR) was 2.65 ± 0.14% (2.48%–2.88%), and diabetic macular edema (DME) was 2.21 ± 0.18% (2%–2.49%). Renal study results were as follows: UACR > 30 mg/g had an annual incidence of 7.02 ± 0.05% (6.97%–7.09%), eGFR < 60 ml/min/1.73 m2 incidence was 5.89 ± 0.12% (5.70%–6.13%). Cox’s proportional regression analysis of DR incidence shows that renal function studied by eGFR < 60 ml/min/1.73 m2 was less significant (p=0.04, HR 1.223, 1.098–1.201) than UACR ≥ 300 mg/g (p<0.001, HR 1.485, 1.103–1.548). The study of STDR shows that eGFR < 60 ml/min/1.73 m2 was significant (p=0.02, HR 1.890, 1.267–2.820), UACR ≥ 300 mg/g (p<0.001, HR 2.448, 1.595–3.757), and DME shows that eGFR < 60 ml/min/1.73 m2 was significant (p=0.02, HR 1.920, 1.287–2.864) and UACR ≥ 300 mg/g (p<0.001, HR 2.432, 1.584–3.732). Conclusions. The UACR has a better association with diabetic retinopathy than the eGFR, although both are important risk factors for diabetic retinopathy.